Comparative study on cervical ripening and labour induction with dinoprostone versus foley’s catheter with extra amniotic saline infusion - A., Rachel Alexander; A., Gigi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Induction of labour is defined as initiation of uterine contractions before spontaneous onset of labour. This observational study compares the effect of prostaglandin E2 (PGE2) and extra amniotic saline infusion (EASI) for pre-labour ripening of unfavourable uterine cervix. Methods: This was a prospective study conducted on 100 pregnant women with gestational age ≥37 weeks during a year period in the department of obstetrics and gynaecology of government TD medical college, Alappuzha, Kerala. The period of study was for one year from June 2002 to July 2003. All patients were divided into two groups. Group-1 contains 47 patients who received intracervical PGE2, (Dinoprostone gel, 0.5 mg). Group-2 contains 53 patients who were induced with EASI. The main outcome variables were the number of subjects with favourable Bishop’s score, mode of delivery, maternal complications and neonatal outcomes. Results: Majority of the patients in both the groups were in the age of 21-30 years. There was significant difference in age, parity and gestational age of both groups. In this study it was found significant difference in the occurrence of hyper stimulation among PGE2 and EASI; whereas, there was no significant difference in the occurrence of maternal pyrexia among two groups. High incidence of caesarean section was found in EASI. APGAR score of new born babies was high in labour induced with PGE2. Conclusions: PGE2 and EASI have similar efficacy in induction of labour, but EASI is associated with more side effects. Cost wise EASI is more cost effective than PGE2.